Impact of Education on Trauma Patients Handover Quality; a Before-After Trial - Shahrami, Ali; Nazemi-Rafi, Masoomeh; Hatamabadi, Hamidreza; Amini, Afshin; Haji Aghajani, Mahammad (Archives of Academic Emergency Medicine, 2019)
Introduction: Poor handover and inadequate transmission of clinical information between shifts cause a lot of problems in patient care and result in significant risks for physicians and patients. This study was designed to evaluate the impact of education and application of handover checklist on trauma patientsâ€™ handover quality. Methods: In this before-after trial, handover process of trauma patients in an educational hospital was evaluated before and after education and application of a handover checklist, abbreviated as â€œWHO MISSED IP?â€, using a questionnaire that consisted of 10 necessary items, which should be delivered during handover of trauma patients. A total score of 10 was considered for each patient handover, the score 10 out of 10 indicating that all 10 important pieces of patient information were correctly delivered. Results: 52 pre and post-intervention handover sessions were evaluated (438 patients). Prior to intervention, 18% of patients were not delivered to the next shift, most of which were in the night shift handover (p < 0.001). From the pre-intervention to the post-intervention period, significant improvements were detected in all items except for diagnosis and consulting items. The mean duration of handover changed from 1.22 Â± 0.24 minutes to 1.58 Â± 0.23 minutes after intervention (p < 0.01). In the pre-intervention period, the score equal or greater than 9 was observed in 7.5% of patients, while after intervention, 63.6% of patients had score â‰¥ 9 regarding complete handover (p < 0.01). Conclusion: Based on the findings of the present study, teaching handover standards and application of handover checklist could be helpful in improving the quality of information delivery between emergency medicine residents and improve trauma patientsâ€™ handover indices.